(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Water is considered to be of paramount importance when it comes to survival of the entire humanity. The chemical formula of water is H2O, which contains two molecules of Hydrogen and one molecule of Oxygen. The need and importance of water has been there since time immemorial as numerous civilizations got settled near the sea coasts/river banks. Empedocles, a Greek philosopher stated, water is one of the five basic elements for individual sustenance. Earth is also known as the blue planet, and per se there is no shortage of water. An approximate amount of 336 trillion gallons of water is present. However, 97% of its water is salty and the remaining 2% lies in trapped snow-capped mountains, hence the world is left with just 1% in the form of potable water to survive. A separate Ministry of Jal Shakti under the aegis of Government of India was formed in May 2019, by merging the two ministries, i.e. Ministry of Water Resources, River Development & Ganga Rejuvenation and Ministry of Drinking Water and Sanitation. As per this ministry, it aims to provide safe drinking water via household tap connections by 2024 in rural areas across the country. The Hon’ble Supreme Court of India in numerous judgments, i.e. Subhash Kumar v State of Bihar considered right to safe drinking water as fundamental right under Article 21 of the Indian Constitution. However, the ground reality is different as the access to safe drinking water as a fundamental right is not expressly stated in the Indian Constitution nor there is any specific legislation on access to safe potable water. Right to safe drinking water is a global concern which is needed to be resolved on top priority.